+0  
 
+1
124
1
avatar+545 

thank you in advance

 

 

winkwinkwink

lynx7  Apr 19, 2018
 #1
avatar+88898 
+3

First one :

 

x2  = (x1)^2  - x1

x2  = (1)^2  - (1)

x2  = 0

 

x3  = (x2)^2  - x2

x3 =  (0)^2 -  0

x3  = 0

 

This pattern  of 0's  will repeat indefinitely...so...the pattern  is  1,0,0,0.......

 

Second one

 

x2  = (x1)^2 - x1         

x2  = (-1)^2 - (-1)

x = 1 + 1

x2  = 2

 

x3  = (x2)^2  - x2

x3  = (2)^2  - 2

x3  = 4  - 2

x3  = 2

 

This pattern of 2's will repeat indefinitely....so....the pattern is   -1, 2, 2, 2......

 

 

 

Last one

 

x2  =  ( 1 - √2)^2  - (1 - √2)

x2 =  (1  - 2√2 + 2)  -1 + √2

x2  = 2 - √2

 

 

 

cool cool cool

CPhill  Apr 19, 2018

20 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.